Multiple gingival recession coverage treated with vestibular incision subperiosteal tunnel access approach with or without platelet-rich fibrin - A case series - Surbhi Garg; Sachit Anand Arora; Shivjot Chhina; Padam Singh (Wolters Kluwer Medknow Publications, 2017)
Background: Gingival recession involves both soft tissue and hard tissue loss. In this evolutionary era of dentistry, newer techniques have evolved for complete coverage of isolated recession defects. Since 2012, vestibular incision subperiosteal tunnel access (VISTA) technique was used with various regenerative membranes to treat multiple recession defects (MRDs). Platelet-rich fibrin (PRF) membrane, a pool of growth factors but have any added advantage to recession coverage techniques is controversial. Thus, in this case series, we compare the effect of VISTA with or without PRF-membrane for the treatment of Classes I and III MRDs. Subjects and Methods: Four patients between of age 30 and 40 years (two patients having bilateral Class I and another two having bilateral Class III MRDs) were selected from the Department of Periodontics, ITS Dental College, Greater Noida and designated as Case I-IV simultaneously. Recession defects at antagonist sites in each patient were corrected by VISTA approach with or without PRF-membrane. Recorded clinical parameters included recession depth, recession width, pocket probing depth, and clinical attachment level (CAL) at baseline and 6 months postoperatively. Results: Patients having Class I recession defects showed almost complete root coverage with VISTA technique alone and reflected no added advantage of PRF-membrane. However, patients with Class III recession defects treated with VISTA + PRF-membrane showed more reduction in recession depth and gain in CAL as compared to sites treated with VISTA only. Conclusion: VISTA alone is a convenient technique for treatment of Class I MRDs. Addition of PRF-membrane for Class III recession defects give better outcome in term of reduction of recession depth and gain in CAL 6 month postoperatively.